PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN - Sianipar, Semy Loanda; Evyanto, Winda (SCIENTIA JOURNAL, 2021)
Trade as an aspect of economic development, for example in traditional trade, where sellers and buyers meet each other in certain places who trade/buy each other or trade electronically (e-commerce). E-commerce trading is a series of seller and buyer transactions that are carried out using an electronic system (internet). An important aspect of trading in e-commerce is the need for transportation services that can open goods shuttle services. The high demand for goods pick-up services makes it a valuable opportunity for logistics businesses. That studies aims determining the effect of Service Quality and Price on Consumer Satisfaction at PT Monang Sianipar Abadi Batam Branch. This researches design using researches designed and quantitatives causality researches methods. Data collection techniques by distributing questionnaires to 225 consumers of PT Monang Sianipar Abadi Batam Branch.The results of this studies are indicating that Service Quality (X1), Price (X2) partially and simultaneously affect significant to Consumer Satisfaction is avout 53.2 percent.